Alpha-7 Nicotinic Receptor Dampens Murine Osteoblastic Response to Inflammation and Age-Related Osteoarthritis - Courties, Alice; Petit, Juliette; Do, Ariane; Legris, Manon; Kouki, Inès; Pigenet, Audrey; Sacitharan, Pradeep K.; Ehkirch, Francois-Paul; Berenbaum, Francis; Sellam, Jérémie (Frontiers in Immunology, 2022)
Introduction: Osteoarthritis (OA) is a whole-joint disease characterized by a low-grade inflammation which is involved in both cartilage degradation and subchondral bone remodeling. Since subchondral bone has a cholinergic innervation and that acetylcholine (Ach) might have anti-inflammatory effect through the a7 nicotinic Ach receptor (a7nAchR); we aimed i) to determine the expression of non-neuronal cholinergic system and nicotinic receptors subunits by murine and human osteoblasts, ii) to address the role of a7nAchR in osteoblastic response to inflammation, iii) to study the role of a7nAchR in a spontaneous ageing OA model. Methods: Primary cultures of WT and a7nAchR knock out mice (Chrna7-/-) murine osteoblasts and of subchondral bone human OA osteoblasts were performed. The expressions of the non-neuronal cholinergic system and of the nAchR subunits were assessed by PCR. In vitro, IL1β-stimulated WT, Chrna7-/- and human osteoblasts were pretreated with nicotine. At 24h, expressions of interleukin-6 (IL6) and metalloproteinases- 3 and 13 (MMP), RANK-ligand (RANKL) and osteoprotegerin (OPG) were quantified by qPCR and ELISA. Spontaneous ageing OA was evaluated and compared between male WT and Chrna7-/- mice of 9 and 12 months. Results: Murine WT osteoblasts express the main components of the cholinergic system and 7 subunit composing a7nAchR. Nicotine partially prevented the IL1a-induced expression and production of IL6, MMP3 and RANKL in WT osteoblasts. The effect for IL6 and MMP was mediated by a7nAchR since nicotine had no effect on Chrna7-/- osteoblasts while the RANKL decrease persisted. Chrna7 -/- mice displayed significantly higher cartilage lesions than their WT counterparts at 9 and 12 months, without difference in subchondral bone remodeling. Human OA osteoblasts expressed also the non-neuronal cholinergic system and a7 subunit as well as CHRFAM7A, the dominant negative duplicate of Chrna7. Nicotine pretreatment did not significantly reduced IL6 and MMP3 production in IL-1B-stimulated human osteoarthritic osteoblasts (n=4), possibly due to CHRFAM7A. Conclusion: Cholinergic system counteracts murine osteoblastic response to IL-1B through a7nAchR. Since a7nAchR deletion may limit cartilage degradation during murine age-related OA, enhancing cholinergic system could be a new therapeutic target in OA but may depend of CHRFAM7A expression.